Factors Influencing the Application of Regional Regulation Number 3 of 2021 Concerning Zakat Management in the City of Gorontalo - Asrul Aswar; Erman I. Rahim (Estudiante Law Journal, 2023)
This study aims to identify the factors that influence the application of these regional regulations. This study uses a qualitative approach by conducting in-depth interviews with several related parties, such as the Gorontalo Municipal Zakat Agency (BAZ), zakat management institutions, and the community. The results of the research show that there are several factors that influence the application of Regional Regulation Number 3 of 2021 concerning Zakat Management in the City of Gorontalo. First, regulatory factors, namely the clarity and consistency of regulations, as well as a deep understanding of the contents of these regulations. Second, institutional factors, such as the capacity and competence of zakat management institutions, support from local governments, and the active involvement of the community in zakat management. Third, social and cultural factors, including people's perceptions of zakat, trust in zakat management institutions, and a culture of mutual assistance in society. This study also found several obstacles in the implementation of these regulations. These obstacles include the lack of public understanding of these regulations, low community participation in zakat management, lack of local government support in implementing regulations, and limited capacity and competence of zakat management institutions. Based on these findings, this study recommends several steps to improve the implementation of Regional Regulation Number 3 of 2021 concerning Zakat Management in the City of Gorontalo. These steps include increasing socialization of regulations to the public, increasing community participation in zakat management, increasing the capacity and competence of zakat management institutions, and strengthening support from local governments.